An analysis of energy, exergy, and sustainable development of a vapor compression refrigeration system using hydrocarbon - Ahamed, Jamal Uddin; Saidur, Rahman; Masjuki, Haji Hassan; Sattar, M.A. (Taylor & Francis, 2012)
Hydrocarbons being natural fluid have drawn much attention of the scientists and researchers for the application as a sustainable material for the vapor compression refrigeration system. This paper presents a comparison of the energetic and exergetic performances of a domestic refrigerator using pure butane and isobutane as refrigerants. The thermodynamic performances such as exergy destruction or losses, exergy efficiency, and coefficient of performances (COP) were investigated. These parameters were measured at varied operating conditions. Exergy and energy efficiencies of isobutane were found to be 50 and 175 higher than that of R-134a. The analysis shows that the performances of butane and isobutane as refrigerants are comparable with HFC134a. It has also been found that at higher evaporating temperatures, the exergy losses are minimal. The maximum exergy loss occurred in the compressor and the value was 69 of the whole losses in the system. Highest sustainability index was found for butane compared to that of R134a and R600a, respectively.